Online Travel Agent Promotions to Increase Room Occupancy - Ni Made Rani Widya Sari; Ni Nyoman Triyuni; I Gusti Agung Mas Krisna Komala Sari; I Ketut Suja; Anak Agung Ayu Ngurah Harmini (Catuspata Press, 2022)
Purpose: This article aims to determine the influence of online travel agent promotions in increasing room occupancy and the effectiveness of online trav-el agent promotions in increasing room occupancy at a 4-star hotel in Ubud, Bali, Indonesia, and to find out which online travel agent platforms play the most effective role in increasing room occupancy. Research methods: The analysis techniques used are series of simple re-gression analysis and effectivity analysis. Findings: Regarding to analysis of effectiveness, online travel agent promotion is very effective in increasing room occupancy with percentage of 106.89 per-cent. Based on the calculation of room night contribution, Booking.com is the most effective online travel agent platform in increasing room occupancy at Wapa di Ume Resort and Spa Ubud with the total contribution 3,287 room nights in period of 2017-2019. The greater of online travel agent promotion carried out, the more the room occupancy in the hotel will increase. Implication: Online travel agent promotions in the form of informing, reminding and persuading activities are very effective in increasing room occupancy.